Alcohol abuse by a family member as a factor modelling the linguistic image of the adult world - Baruk‑Dzięcioł, Ewa (Rodzina w systemie wsparcia i pomocy osobom z problemem alkoholowym, 2020)
Alcohol abuse by a family member is one of the factors responsible for the development of this dysfunction. When present in a family environment, this issue has a deforming effect on the other members’ perception and interpretation of reality. Hence, the image of themselves and the world around them which forms in their minds is often inadequate and false. Therefore, the question arises of whether alcohol abuse by a family member can be a factor modelling the linguistic image of the adult world. The answer to this question can be sought in the results of an association experiment conducted among people from families affected by alcohol abuse and from those unaffected by it, using stimuli words addiction and alcoholism. It was observed that the prototype of the linguistic image of addiction is very similar, both because of its denotation in female respondents in individual groups, and because of the ranking positions occupied by its constituent associations. However, the frequency of the use of specific associations was different for individual groups of respondents. This indicates that they perceive the significance of specific elements in the linguistic image of addiction differently. It also appears that that prototype of the linguistic image of alcoholism has a similar denotation. However, the associations which constitute it are not only used with different frequency, but they also occupied different ranking positions in replies by female respondents in different groups. In conclusion, the study suggests that addiction is an element of the linguistic image of the world that largely depends on socio cultural and educational impact. On the other hand, the linguistic image of alcoholism in the group of respondents is susceptible to the modelling effect of the presence of a family member who abuses alcohol.